Feasibility study of partial separation continuous high-speed ultrasonic vibration cutting Inconel 718 - Zhiyong Huang; Jiteng Li; Mingshuo Zhang; Xinggang Jiang; Daxi Geng; Deyuan Zhang (Journal of Materials Research and Technology)
Ultrasonic vibration assisted-cutting (UVAC) can improve the tool life by cutting intermittently to open the cutting area for cooling and lubrication, which includes traditional ultrasonic vibration cutting (UVC), elliptical ultrasonic vibration cutting (EUVC) and high-speed ultrasonic vibration cutting (HUVC). However, only when the conditions of intermittent cutting are met, compared with the conventional cutting (CC), the good effects of UVAC can be achieved, which limits the improvement of material removal rate (MRR). Therefore, this article proposed a new type of ultrasonic vibration cutting, i.e. partial separation continuous high-speed ultrasonic vibration cutting (C-HUVC). This method partially opens the cutting area during continuous cutting, so solves the contradiction between opening the cutting area and improving the MRR in UVAC. Firstly, the theoretical model of C-HUVC process was established, and then the feasibility of high MRR cutting Inconel 718 by C-HUVC method was verified by comparing with CC. The results show that under the best conditions, compared with CC, C-HUVC produces an 18.33% reduction in cutting temperature, a 20.85% reduction in main cutting force, a 23.84% reduction in axial thrust force, a 105.29% increase in tool life and a 200% increase in MRR.